AZ-900 Microsoft Azure Fundamentals Certification 2020 - Nednur, Anand (Packt Publishing, 2020)
Prepare for the Microsoft AZ 900 exam with the help of mock tests and case studies About This Video Explore diagrams, pictorial representations, and live demos to grasp concepts and reinforce the learning Understand the fundamentals of Azure using real-world, enterprise-level cloud projects Cover key points involved in migrating complex infrastructure In Detail Exam AZ-900 is designed for candidates looking to demonstrate foundation-level knowledge of Microsoft Azure cloud services. This exam can be taken as an optional first step in learning about cloud services and how those concepts are exemplified by Microsoft Azure. It can be taken as a precursor to Microsoft Azure or Microsoft cloud services exams. While it is a beneficial first step, validating your fundamental knowledge, taking this exam is not a prerequisite for any other Azure certifications. By the end of this course, you'll be fully equipped with the knowledge required to pass the AZ-900 exam. If you're looking for an entry point to Microsoft Azure, this AZ-900 exam prep course is what you need!